Nationwide survey: what is important for a sustainable radiology? = Bundesweite Umfrage : was ist wichtig für eine nachhaltigere Radiologie? - Palm, Viktoria; Wucherpfennig, Lena; Do, Thuy; Fink, Matthias A.; Stackelberg, Oyunbileg von; Schwaiger, Benedikt; Kauczor, Hans-Ulrich (RöFo, 2024)
Radiology departments with the large diagnostic devices CT and MRI contribute significantly to the overall energy consumption of health facilities. However, there is a lack of systematic knowledge about the opinions of radiological staff on the most relevant aspects of sustainability. For this reason, we conducted a comprehensive survey for radiology employees on sentiment and experiences regarding sustainability in radiology. - - In collaboration with the Sustainability Network of the German Roentgen Society (DRG), we developed a questionnaire on various dimensions of sustainability in radiology. We conducted a nationwide online survey of radiology employees between July 1st, 2023 and November 30th, 2023. The absolute and percentage distributions were then determined. - - From 109 participants, mainly doctors (67/109; 62%) from university hospitals (48/109; 44.0%), 81 out of 109 rated sustainability in professional environment (74.3%) as important or very important. However, only 38 out of 109 (38%) of the respondents were able to name specific sustainable procedures in their institute. The most important topics for a sustainable radiology were waste management (26/109, 22.6%), energy reduction (19/109, 16.5%), conscious behaviour (15/109, 13%) and reduction of obsolete examinations (14/109, 12.2%). In addition, a lack of qualifications (16%), finances (21%) and compliance (21%) were named as challenges for the implementation of sustainable actions in radiology. The perceived importance of specific, sustainable measures in radiology is generally higher than the amount of already established actions. - - Radiology has significant, yet untapped, potential for sustainable optimization. There is a need for qualified and sensitized health care workers in radiology who are committed to sustainability in everyday clinical practice. Among other things, in this study the respondents demand a more critical indication for diagnostic workup, including avoiding redundant examinations, and a technological progress towards energy-efficient devices, which requires a dynamic exchange between radiology, industry and health care facilities.